The status of oral hygiene in cleft lip, palate patients after surgical correction - Pandey S; Pandey R (Wolters Kluwer Medknow Publications, 2005)
The cleft lip and palate patients usually present a number of problems viz. altered oral anatomy leading to changes in oral physiology diminishing the self-cleansing ability of individual. The handicapped children are unable to maintain their oral hygiene properly. The present study was formulated with the aim that does normalization of oral anatomy have its effect on improvement of oral hygiene? An assessment of oral hygiene index-simplified was performed between preoperative and postoperative values in the same patient at KGMU and KGDU. A total of 50 cases were recorded in two groups of 25 each: (i) < 6 years old and (ii) > 6 years. The observations are statistically analyzed by paired ′t′ test to get the significance of results. Results: The data analyzed showed the significant decrease in oral hygiene indices observed in both groups. A relative significance in oral hygiene status following surgery was observed. Both groups expressed greater significance when compared pre and postoperatively which is indicative of considerable improvement of oral hygiene after surgical correction. The study concludes that oral hygiene improves more in older cleft lip-palate cases following reconstruction of palatal vault, premaxilla and anterior lip seal by secondary bone grafting method when compared with oral hygiene indices results in primary periosteoplasty cases. The surgical correction of cleft lip palate enhances self-cleaning ability and better compliance to maintain oral hygiene in children as the age advances.